(untitled) - Eastop, T. D. (New York, 1993)
...The chapter on energy resources use and management (ch17), has been impoved and extended; it now includes a more extensive coverage of combined heat and power and a new section on energy recovery,...
Keywords: Thermodynamics,Nhiệt động lực học